Acceptability of an Alimentary Supplement of Whey-Protein Concentrate and TGF-β in Patients with Crohn's Disease. (21st July 2013) - Davanço, Taciana; Silva, Luciano Bruno de Carvalho; Sampaio, Karina de Lemos; Coy, Cláudio Saddy Rodrigues; Vilela, Maria Marluce dos Santos; Pinto, Elizete Aparecida Lomazi da Costa
Abstract : The objective of this study was to evaluate the acceptability of an alimentary supplement of bovine whey-protein concentrate (WPC) and TGF- β, unavailable commercially, by patients with Crohn's disease (CD) and determine the chemical composition, solubility, and total amino acids content. The supplement was diluted in water, and an acceptance test was done to evaluate the aroma, flavour, and viscosity of the product using facial hedonic scale (nine-point scale), applied on 54 CD patients. The supplement composition indicated 73.3% protein, 10.5% fat, 2.2% ash, 6.3% water, and 7.7% carbohydrate. The supplement is presented as a good protein source and high content of essential amino acids. The average acceptance for all the attributes was between 5.0 and 6.0, and the flavour was mainly associated with soybean/grain, sour milk, and sweet/vanilla flavour. The results indicated that the supplement provided important nutritional properties for CD patients; however, for a large number of individuals to be encouraged to perform supplementation, it is essential to improve the sensory quality of the product. In order to do so, additional research is necessary to prevent the formation of volatiles which cause off-flavours or to mask undesirable aromas/flavours found in it.